Gender norms and intrahousehold allocation of labor in Mozambique: A CGE application to household and agricultural economics. (25th February 2020) - Arora, Diksha; Rada, Codrina
Abstract: We model intrahousehold dynamics in two rural provinces of Mozambique through the lens of computable general equilibrium (CGE) methods. The main features of our modeling framework are as follows: (a) a household social accounting matrix that captures allocation of labor and resources, and transfers among household members; (b) the explicit use of social norms in labor allocation across gender; (c) a mechanism that links agricultural production to time poverty; (d) identification of leisure as a commodity that is being produced. Simulation results and sensitivity analyses show how social norms interact with the allocation of labor and resources at the household level to impact farm production or limit the gains from technological improvements.